Persimmon leaf extract in dyslipidemia: a systematic review and meta-analysis - Dong, Chenxuan; Chang, Tianying; Wang, Xiaoli; Zhou, Lei; Wang, Lisha; Wang, Xiaodan; Sun, Yu; Liao, Xing; Cui, Yingzi; Guo, Jiajuan (Frontiers in Pharmacology, 2025)
AimThis study aims to evaluate the effects of the combined application of Diospyros kaki Thunb. [Ebenaceae; Kaki folium] (Persimmon leaf) extract on lipid profiles in adults and to explore its potential role in preventing and treating lipid disorders and associated diseases, including common comorbidities such as cardiovascular and cerebrovascular diseases, as well as medication-induced dyslipidemia.MethodsFrom the inception of the database to 1 November 2024, we retrieved randomized controlled trials (RCTs) from eight English and Chinese databases.ResultsA total of 704 articles were retrieved, from which 16 studies were selected for inclusion in the systematic review and meta-analysis. These studies encompassed 1,572 patients, with 790 assigned to the treatment group and 782 to the control group. Among the dyslipidemia patients included in the study, the most common comorbidities were coronary artery disease, hypertension, ischemic cerebrovascular disease, and dyslipidemia induced by olanzapine, among others. Compared with the control group, the use of combined Persimmon leaf extract (PLE) significantly reduced total cholesterol (TC), triglycerides (TG), and low-density lipoprotein cholesterol (LDL-C) levels, while demonstrating a certain degree of improvement in high-density lipoprotein cholesterol (HDL-C) levels.ConclusionPLE has been shown to be effective in improving blood lipid profiles in patients, suggesting its potential for widespread clinical application. However, the significant heterogeneity observed across existing studies, coupled with the frequent occurrence of methodological flaws, emphasizes the need for well-designed clinical trials with large sample sizes and extended follow-up periods.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=562090, identifier CRD42024562090.